The forests of Veracruz in the context of a REDD+ state strategy - Gerez-Fernández, Patricia; Pineda-López, María del Rosario (Instituto de Ecología, A.C., 2016)
Nowadays, forests have a key role to mitigating the effects global warming has on our planet. Scientific knowledge on ecosystem processes and services to human wellbeing confirm this. As an important component on REDD+ national and regional strategies, which will guide the actions needed to reduce and mitigate the greenhouse gases emissions, forest management and forest conservation are the most effective and less costly measures. This kind of strategies will contribute directly to improve the life conditions of forest owners, and socioeconomic development conditions of forest regions. Even though Veracruz state has developed a Law and an Action Plan towards Climate Change, a REDD+ perspective is still a novelty. It constitutes an opportunity for academic collaboration with government institutions on the three levels, with forest owners, and with those involved in forestry activity along the state. In this context, we present a general analysis on Veracruz´ forests situation, pointing out the deforestation and degradation trends and active processes, to outline certain aspects as opportunity areas to develop collective efforts between academia and forest owners, to improve the management of our forest ecosystems for the benefit of society.